Cross - modal perceptions in Mandarin and Cantonese - Lye, Guinevere Shuen Yi (2015)
The interaction of vision and audition has long been established in cross-modal correspondence literature. Pitch has also been extensively studied in this regard. However, few studies have examined how language plays a role in vision-audition correspondences. A previous study found that the pointiness of an object was associated with increasing amounts of pitch change in a tone. The present study attempted to compare speakers of two different tonal languages, Mandarin and Cantonese, on the same task using Cantonese tones, which differ from the Mandarin tonal system. The results of the study found that there were no group differences, and that pitch change alone was not sufficient to explain sound-shape matching results. Instead, it was found that pitch change accounted for the results of the contour tones (with one exception), while pitch height accounted for the results of the register tones. The fact that both speaker groups performed the sensory matching task in the same way has implications in whether linguistic processing restricts or limits the way in which we perceive things in our daily life.